Knowledge, attitude and practice of diabetic retinopathy amongst diabetic patients in a tertiary care hospital of Jammu - Sharma, Pallavi; Raina, Bhavani; Bharti, Anuradha (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus is a common metabolic disorder which is characterized by elevated blood sugar level. It is a major cause of blindness in our country, which is preventable and treatable, if healthy practice and knowledge regarding this disease is applied. The study was undertaken to assess the knowledge, attitude and practice of Diabetic Retinopathy, amongst diabetic patients attending eye OPD in GMC Jammu. Methods: 300 patients diagnosed with diabetes mellitus attending eye OPD, over a period of 10 months, in GMC Jammu, were incorporated in this study. Self administered questionnaires were used to assess knowledge, practice and attitude of diabetic retinopathy amongst the diabetic patient, after their due consent. Results: This study incorporated 300 diabetic patients out of which 168 (56%) were males and 132 (44%) were females. Most of the patients (70%) were aware of the fact that diabetes can cause eye disorders. 67.33% believed that they should go for regular eye check-ups. 79.33% agreed that timely intervention can delay the complications in diabetic eye disease. Conclusions: Diabetes can lead to serious ocular complications which can be prevented by appropriate awareness and optimistic attitude and good approach towards the disease.